CAMU-CAMU (Myrciaria dubia (HBK) McVaugh), a small Amazonian fruit rich in vitamin C and a supplement for immunity (Research, Society and Development, 2021)
The Amazon Rainforest is rich in a diversity of species with various bioactive properties that have been widely used to treat a variety of inflammatory diseases. During the infection process, an oxidative stress environment is created that leads to cellular damage mediated by the transcription factor NF-kB, and triggers the production of pro-inflammatory chemical mediators, such as tumor necrosis factor-α [TNF-α] and interleukins IL-1β, IL-6, which causes a decline in the immune system. In this sense, the camu-camu fruit, which is native to the Amazon region, has in its nutritional composition several bioactive compounds and the highest level of vitamin C among Brazilian tropical fruits. It is also noted for its antioxidant and anti-inflammatory properties. Therefore, the objective of this review is to analyze the evidence collected in the literature regarding camu-camu as a functional food for the immune system in oxidative and inflammatory events.